PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA SD - Saputra, Ananda Eko; Kartono, Kartono; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis purpose of this research to analyze the influence application of the Problem Based Learning model the learning outcomes of students in learning Scienceclass Vstate Primary School South-eastPontianak. The method used is experimental method with quasi experimental design with Nonequivalent Control Group Design. The population in this research is class V which is 190 students. The sample in this research is VA (experiment class) which is 22 students and class VB (control class) which is 22 students. Based on the result of the calculation of the mean of student learning outcomes (post-test) control class equal to 60.59 and mean of student learning result (post-test) experiment class 69.55 obtained tarithmetic equal toÂ 3.2719and t table Î± = 5% Of 1.6827, which means t arithmetic > t table (3.2719> 1.6827), then Ha is accepted. From the calculation of effect size obtained 1.01 (high criterion). This means that there is an effect of the application of Problem Based Learning model to the learning outcomes of Science of class Vstate Primary School South-eastPontianak.Â Keyword:Influence, Problem Based Learning Model, Learning Outcomes, Science